2019
DOI: 10.1051/epjconf/201921501005
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization and additive manufacturing of an optical housing for space applications

Abstract: The design of an optical housing for laser telecommunication in space is improved by topology optimization. Different mechanical and thermal boundary conditions are considered while minimizing the overall weight of the housing. As a proof-of-concept study, a complex and lightweight housing is made by additive manufacturing with the aluminium silicon alloy AlSi40. Post processing steps include a thermal treatment, cleaning and a mechanical machining process. Final characterization tests include the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The connection between the prisms and the bipods is formed by Invar pins which are glued to both partners of the joint. To suppress stray light and disturbance light, the prisms are enclosed in two ultra-light and blackened covers, which are additively manufactured at the IOF using Selective Laser Melting (SLM) [2].…”
Section: Mechanical Designmentioning
confidence: 99%
“…The connection between the prisms and the bipods is formed by Invar pins which are glued to both partners of the joint. To suppress stray light and disturbance light, the prisms are enclosed in two ultra-light and blackened covers, which are additively manufactured at the IOF using Selective Laser Melting (SLM) [2].…”
Section: Mechanical Designmentioning
confidence: 99%
“…Hypereutectic Al-high Si alloys, especially with Si content > 30 wt.%, are characterized by preeminent properties, like low density, low thermal expansion, high hardness and stiffness, and excellent wear resistance, which enable numerous applications in the automotive, space and electronics industries [ 1 , 2 ]. All the alloy properties mentioned improve with increasing Si content, hence, there is high industrial interest regarding the commercial availability of AlSi-alloys with Si-content ≥ 50 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, Heidler et al 8 demonstrated that topology optimisation and AM can be used to reduce the mass of an optical housing for a space application by 20% and Frasch et al 3 used generative design tools to optimise the design of the structure for a three-mirror beam expander. In Frasch et al the original component was 150 mm×90 mm×90 mm weighing 0.5 kg.…”
Section: Introductionmentioning
confidence: 99%